2021
DOI: 10.3390/cancers13174487
|View full text |Cite
|
Sign up to set email alerts
|

Organ-Chip Models: Opportunities for Precision Medicine in Pancreatic Cancer

Abstract: Pancreatic Ductal Adenocarcinoma (PDAC) is an expeditiously fatal malignancy with a five-year survival rate of 6–8%. Conventional chemotherapeutics fail in many cases due to inadequate primary response and rapidly developing resistance. This treatment failure is particularly challenging in pancreatic cancer because of the high molecular heterogeneity across tumors. Additionally, a rich fibro-inflammatory component within the tumor microenvironment (TME) limits the delivery and effectiveness of anticancer drugs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 121 publications
0
13
0
Order By: Relevance
“…Cancer applications include I) the incorporation of multiple cell types, like those typically present in the TME, to allow the study of the interactions between cancer cells and surrounding tissues, II) the modeling of microvascular networks to assess antiangiogenic drugs and study tumor vascular perfusion; III) the study of cancer cells' extravasation and migration to induce metastasis formation. [664] Due to their ability in recapitulating the microenvironments of in vivo tissues, OOC models have been applied to pancreatic cancer with the final aim of providing a complex multicellular model of human PDAC on a chip, designed for drugs and therapeutics testing. One of the first applications included an in vitro model consisting of pancreatic stellate cells cocultured with PDAC cells in an accessible 3D construct with a spatially controlled architecture, which was proposed as an alternative platform for drug evaluation.…”
Section: Organs-on-chipmentioning
confidence: 99%
See 1 more Smart Citation
“…Cancer applications include I) the incorporation of multiple cell types, like those typically present in the TME, to allow the study of the interactions between cancer cells and surrounding tissues, II) the modeling of microvascular networks to assess antiangiogenic drugs and study tumor vascular perfusion; III) the study of cancer cells' extravasation and migration to induce metastasis formation. [664] Due to their ability in recapitulating the microenvironments of in vivo tissues, OOC models have been applied to pancreatic cancer with the final aim of providing a complex multicellular model of human PDAC on a chip, designed for drugs and therapeutics testing. One of the first applications included an in vitro model consisting of pancreatic stellate cells cocultured with PDAC cells in an accessible 3D construct with a spatially controlled architecture, which was proposed as an alternative platform for drug evaluation.…”
Section: Organs-on-chipmentioning
confidence: 99%
“…Cancer applications include I) the incorporation of multiple cell types, like those typically present in the TME, to allow the study of the interactions between cancer cells and surrounding tissues, II) the modeling of microvascular networks to assess antiangiogenic drugs and study tumor vascular perfusion; III) the study of cancer cells’ extravasation and migration to induce metastasis formation. [ 664 ]…”
Section: Nanoparticle‐based Medicine and Theranostic Approachesmentioning
confidence: 99%
“…Thus, a preliminary sequencing of the DNA of patients and mutation status could give an indication of the type of drugs that should be tested on organoids and afterwards prescribed to a given patient. Moreover, Haque et al recently discussed the impact of the heterogenous TME in PDAC and concluded that extensive model development is still needed for establishing efficient drug pipelines ( Haque et al, 2021 ). Therefore, current in vitro model systems are lacking in translational value, and novel PDAC models that allows for rapid initial drug testing that provide a truly translational outcome for identifying novel patient treatment options are called for.…”
Section: Current In Vitro Models Used For Drug Screeningsmentioning
confidence: 99%
“…16 For these reasons, current research is focusing on the development of in vitro PDAC models for a deeper understanding of this pathology, the identification of new biomarkers and the establishment of screening tests, in order to enable the earlier detection of pancreatic cancer and improve the prognosis. [17][18][19][20][21][22] However, one of the major limitations of PDAC in vitro models is the difficulty in replicating the tumor microenvironment surrounding the gland and the PDAC-stroma crosstalk, which constitutes an important feature that significantly affects tumor evolution and drug resistance. [22][23][24][25][26] Among the existing in vitro models, organ-on-achip microfluidic systems represent a powerful tool to reproduce the cancer cell-stroma interactions in a controllable environment and under real-time monitoring.…”
Section: Introductionmentioning
confidence: 99%